\(^{=x^3-3x^2+5x^2-15x+9x-27}\)
\(=x^2\left(x-3\right)+5x\left(x-3\right)+9\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
\(x^3+2x^2-6x-27\)
\(=x^3+5x^2+9x-3x^2-15x-27\)
\(=x\left(x^2+5x+9\right)-3\left(x^2+5x+9\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
ts cld b lv ag
Phuong Nguyen giải giúp mik bài này đc hk
phan h da thuc sau thành nhân tử ab(x^2+y^2)-xy(a^2+b^2)
\(=ab\left(x^2+y^2\right)+xy\left(a^2+b^2\right)\)
\(=abx^2+aby^2+xya^2+xyb^2\)
\(=xb\left(ax+yb\right)+ay\left(by+ax\right)\)
\(=\left(xb+ay\right)\left(ax+by\right)\)